Students’ Ability in Understanding Dangling Modifiers at Universitas Negeri Padang - Humaira Utami Putri; Sitti Fatimah (Universitas Negeri Padang, 2020)
Dangling modifiers is a problem in sentence structure where there is a mismatch between what the writer or speaker means and what the reader or listener means. This problem will certainly cause a misunderstanding. This study aimed to determine the ability of students to understand dangling modifiers and find out the types of dangling modifiers that were most frequently answered incorrectly by students. This research is a descriptive quantitative study. The population of this study was 35 students from K-2017 English Language Education. Samples were taken using the stratified cluster sampling method. Data were collected through grammar test. The data were given a general score and each part of the test is designed to determine students' ability in understanding dangling modifiers. It was found that the ability of third-year students to understand dangling modifiers was poor because the average score was 49. To find out the type of dangling modifiers that were most answered incorrectly, each answer error in each type of dangling modifiers would be added so that found 55% errors in dangling elliptical clause type. It can be concluded that students need to be aware of logic and illogical sentences (dangling modifiers).